The effect of using language learning strategies in teaching Arabic on the development of Some language skills of primary school students - Abdelkader, Mahmoud Helal (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the effect of using language learning strategies in teaching Arabic on the development of some language skills (reading and writing) among fifth grade students; To achieve this goal, research materials and tools were prepared, which consisted of student worksheets, teacher guide, and language skills test (reading and writing). With two groups, the search experiment was implemented, then the search tools were applied remotely, then the results were processed statistically using the SPSS program. The research found that there were statistically significant differences between the mean scores of the experimental and control groups at the level (0.05) in the language skills test (reading) in favor of the experimental group, and there were statistically significant differences between the mean scores of the experimental and control groups at the level (0.05) in the language skills test. Writing) for the benefit of the experimental group, and there is a correlation between the development of reading skills and the development of writing skills in the post application for the students of the experimental group.